USE OF INNOVATIVE TECHNOLOGIES IN THE VOCATIONAL TRAINING SYSTEM FOR SCHOOLCHILDREN (Proceedings of International Educators Conference, 2024)
In this article, we talk about the importance of innovative educational technologies in today's advanced educational environment. We have been given information about ways to make education more effective, how to use modern technologies during the lesson. Because the knowledge acquired at school serves as a foundation for students to grow up as mature individuals in the future. Today, modern pedagogues use various educational technologies in the course of the lesson to improve the effectiveness of the lesson and improve the quality of education. Through the use of these innovative technologies, the effectiveness of the educational system increases, students better understand hunting materials. After all, the future of our country is in the hands of these young people, therefore, young people should grow up to be well-rounded individuals.